THE USE OF INNOVATIVE TACTICS AND TECHNOLOGIES, AS WELL AS THE SPECIFICS OF THEIR USE IN THE TECHNICAL AND FORENSIC SUPPORT OF PRE-TRIAL PROCEEDINGS FOR CRIMES COMMITTED IN CYBERSPACE - Sabirbaeva Aynura Baxit qizi (Scholar Express Journals, 2025)
The article examines the possibilities of innovation technologies, including artificial intelligence, in the course of solving and investigating crimes committed in cyberspace, and also examines some of the tools used by specialists to collect and record digital evidence.
Keywords: Cybercrime; artificial intelligence; digital evidence